The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.est.2c04998
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake Contributed the Most to Chlorinated Paraffin Body Burden in a Norwegian Cohort

Abstract: Determining the major human exposure pathways is a prerequisite for the development of effective management strategies for environmental pollutants such as chlorinated paraffins (CPs). As a first step, the internal and external exposure to CPs were quantified for a well-defined human cohort. CPs in participants' plasma and diet samples were analyzed in the present study, and previous results on paired air, dust, and hand wipe samples were used for the total exposure assessment. Both one compartment pharmacokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…A recent published study identified that dietary intake was the most predominant source of daily CP intake, contributing up to 88%, 82% and 60% of the total SCCP, MCCP and LCCP intake, based on a Norwegian cohort using one compartment pharmacokinetic modeling and forensic fingerprinting. 28 CPs were ubiquitously detected in various foodstuffs and considered accumulated in animal-sourced foods due to the high lipophilicity and persistence of CPs. 1,26,67 The calculation equation for the EDI of CPs via dietary intake was listed in ESI Table S2 † 34,65.…”
Section: Health Risk Assessment Of Cps In Humansmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent published study identified that dietary intake was the most predominant source of daily CP intake, contributing up to 88%, 82% and 60% of the total SCCP, MCCP and LCCP intake, based on a Norwegian cohort using one compartment pharmacokinetic modeling and forensic fingerprinting. 28 CPs were ubiquitously detected in various foodstuffs and considered accumulated in animal-sourced foods due to the high lipophilicity and persistence of CPs. 1,26,67 The calculation equation for the EDI of CPs via dietary intake was listed in ESI Table S2 † 34,65.…”
Section: Health Risk Assessment Of Cps In Humansmentioning
confidence: 99%
“…Dermal contact of CPs was proved by the identification of CPs in dust samples from resident living rooms, offices, sports courts and shopping malls, 29,65,74,75 and more direct evidence includes hand wipe samples and silicone wristbands. 28,32 It has been reported that dermal intake can contribute up to 14% of the total MCCP and 29% of the total LCCP intake. 28 The calculation equation for the EDI via dermal absorption of CPs is listed in ESI Table S2 † 1,32,78.…”
Section: Health Risk Assessment Of Cps In Humansmentioning
confidence: 99%
See 3 more Smart Citations